Building Capacity for Creativity: Rediscovering the Inner "Superhero" as a Mechanism for Developing a Creative Mindset for Entrepreneurial Problem-Solving. (January 2021) - Fleck, Emma; Asmuth, Jennifer
This article delivers a series of activities which help participants to examine and stimulate their capacity for creativity to support entrepreneurial problem-solving. It provides a series of tools which enable entrepreneurship educators to support their students in a review, immersion and reflection of their creative capacity using the concept of childhood play, and specifically the superhero, to stimulate their imagination. Inspired by the creative mindset often found in young children, these activities help to build creative self-efficacy, challenging participants to exercise curiosity to go beyond their current resource limitations to solve problems by immersing them within a positive childhood experience. While students explore the concept of creativity and its fundamental role for entrepreneurial problem-solving, the workshop activity helps them to embody their own "superhero" and revisit their unconstrained, imaginative 5 year old selves through the use of pictures, costumes, masks, and icons. Finally, in reflecting upon the activities and acknowledging their own personal capacity for developing a creative process, participants are encouraged to use these skills for problem-solving both within the exercises of the class and throughout their entrepreneurial journey.